Dampak Sosial Ekonomi Perkebunan Karet Terhadap Masyarakat Sekitarnya (Studi Kasus di Desa Lengkong Kecamatan Cipeundeuy Kabupaten Subang). - Erlangga, Reza; Wiyon, Sulistyodewi Nur; Mukti, Gema Wibawa; Fatimah, Sri (Universitas Galuh, 2024)
This research was conducted in Lengkong Village, Cipeundeuy District, Subang Regency, West Java Province, from February to April 2024 with the aim of analyzing the social and economic impact of rubber plantations on the surrounding community. The sampling method used was purposive sampling, namely selecting 10-15% of the available sample population. A total of 15 tapping workers were selected as samples, which is 10% of the total 150 tapping workers in Lengkong Village. Meanwhile, 15 households around the rubber plantation were also taken as samples, in line with the number of tapping workers sampled. The main data analysis was carried out using a qualitative approach, where the results of interviews and observations were recorded in detail in field notes, which were then analyzed descriptively. The research results show that there is a socio-economic impact from the presence of rubber plantations for the surrounding community, both tapping workers and non-tapping workers. This impact can be seen through increasing welfare through the various facilities provided. These facilities include housing, health services, education, places of worship, sports facilities, employment opportunities and sources of income. All facilities provided by the company are intended for the general benefit of the surrounding community, marking mutually beneficial cooperation between the rubber plantation company and the surrounding community.